The art of Islamic banking and finance : tools and tehniques for community-based banking - Yahia Abdul-Rahman , 1944- (The Wiley finance series, 2010)
The Art of Islamic Banking and Finance is a modern take on what it means to incorporate Islamic finance principles into everyday banking and investment techniques. * The author explores the concept of Riba (or interest) and how Islamic finance rules prohibit the use of interest in banking techniques